Internet connectivity disruption in Vietnam (Vietnam) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Vietnam. Data sourced from IODA.
Network Disruption Incident ID: VN-2026-0075. Severity: critical. Confidence: 65%